The Impact of TRIO Student Support Services on Non-traditional Students at a Public State College in Georgia - Bennett, Christopher Aaron, Jr. (My University, 2017)
Higher education institutions are experiencing an increase in enrollment of non-traditional students. Academic support programs such as TRIO Student Support Services (SSS) are funded by the U.S. Department of Education to support college students to persist and graduate from college. The goal of this mixed methods case study was to investigate the impact of the TRIO SSS program on the graduation rates, cumulative grade point averages, retention rates, and the perceived experiences of its recent graduates who were non-traditional students at a public state college in Georgia. The graduation rates, cumulative grade point averages, and retention rates of TRIO SSS participants were compared to students who were also qualified but not served by the TRIO SSS program. A total of 480 non-traditational TRIO SSS and non-TRIO SSS students were involved in the quantitative data analysis, and eight former TRIO SSS students were interviewed during focus groups. Quantitative data analysis resulted in a positive trend of non-traditional TRIO SSS participants’ academic performance and significant differences in graduation rates and retention rates between participants and non-participants. Although the results did not yield a significant difference in cumulative grade point averages between non-traditional TRIO SSS participants and non-TRIO SSS participants, the cumulative grade point averages of TRIO SSS participants were higher than non-participants. The TRIO SSS graduates from focus groups reported TRIO SSS enabled them to be successful in completing their degree programs by providing 1) academic advisement, 2) degree planning, 3) development of self-confidence through motivation and mentorship, 4) academic resources, and 5) a family-oriented environment. These findings were consistent with the framework of Tinto’s theory of student departure. Implications for practice included, but not limited to, additional support for non-traditional students, an inclusive campus culture, and campus personnel devoted to student success. Recommendations for future research included expanding this study by investigating the impact of TRIO SSS programs at other campuses and gathering perceptions of non-traditional students via multiple focus groups.
Chapter I: INTRODUCTION ..1 | Problem Statement 6 | Purpose 6 | Research Questions 8 | Theoretical Framework 8 | Methodology 10 | Significance 11 | Limitations and Assumptions 12 | Definition of Key Terms 12 | Chapter II: LITERATURE REVIEW 14 | Non-traditional Students 14 | Non-traditional Students’ Characteristics 15 | Non-traditional Enrollment Reasons 17 | Barriers for Non-traditional Students 18 | Academic Support for Non-traditional Students 19 | Persistence and Retention 21 | Retention of Disadvantaged Students 22 | History of TRIO Programs 24 | Student Support Services 25 | Tinto’s Theory of Student Departure 27 | Pre-Entry Attributes 29 | Initial Intentions, Goals, and Institutional Commitments 29 | Institutional Experiences 30 | Integration 31 | Later Goals and Commitments 31 | Non-traditional Students in TRIO SSS Programs 32 | Profile of the TRIO SSS Program 33 | National SSS Profile Reports 2001-2002 34 | National SSS Profile Reports 2002-2003 and 2003-2004 35 | National SSS Profile Reports Summary 36 | National Longitudinal Study of the SSS Program 37 | Longitudinal Study Findings 39 | Other Student Support Services Studies 41 | Chapter III: METHODOLOGY .43 | Research Questions 43 | Research Design 44 | Quantitative Approach 45 | Qualitative Approach 45 | Population, Site Information, and Sample Selection 46 | Instrumentation 48 | Validity and Reliability 49 | Data Collection Procedures 50 | Data Analysis 52 | Quantitative Data 52 | Qualitative Data...53 | Chapter IV: DATA ANALYSIS 54 | Research Question 1..54 | Research Question 2..58 | Research Question 3 .....60 | Research Question 4..61 | Research Question 5..62 | Obstacles Encountered as a Non-traditional Student......64 | TRIO SSS’s Role in Overcoming Obstacles ......66 | The Role of the TRIO SSS Staff.....70 | The Top Three Helpful Services Offered by TRIO SSS.72 | Enhancements for the TRIO SSS Program..73 | Recommending TRIO SSS .....74 | Integrating Quantitative and Qualitative Data...74 | Chapter V: FINDINGS AND RECOMMENDATIONS .76 | Discussions of the Findings...76 Implications for Practice....79 | Additional Support for Non-traditional Students....80 | Inclusive Campus Culture....80 | Quality of Personnel....81 | Recommendations for Further Research82 | Conclusions....83 | REFERENCES 86 | APPENDIX A: Permission to Conduct Study Email Template 97 | APPENDIX B: Participant Consent Statement (For Focus Group) 100 | APPENDIX C: Focus Group Interview Questions 103 | APPENDIX D: Valdosta State University Institutional Review Board Approval 105 | APPENDIX E: Institutional Review Board Site Approval..107 |
Keywords: United States. Office of Postsecondary Education. Office of Federal TRIO Programs; Adult education students; Graduation (School); Graduation rates; Education--United States--Georgia